Pregnancy and the Biliary System - Helga Witt; J Joseph Connon (Canadian Journal of Gastroenterology)
Alterations in the synthesis and secretion of bile salts and cholesterol and in gallbladder function occur during pregnancy. These changes are related to the effects of estrogen and progesterone. Biliary cholesterol saturation and the cholic acid/chenodeoxycholic acid ratio increase. Progesterone also diminishes gallbladder contractility and emptying. Gallstones occur in 2.5 to 11% of pregnant women and are associated with cholecystitis in 0.008 to 0.1% of pregnant women. Operative treatment should be deferred if possible until after delivery; failing that, surgery is best done in the second trimester. Endoscopic pap1llotomy may prove to be the best therapy for choledocholithiasis.